Highly efficient nickel-catalyzed 2-methyl-3-butenenitrile isomerization: applications and mechanistic studies employing the TTP ligand family - Tauchert, Michael E.; Warth, Daniel C. M.; Braun, Sebastian M.; Pundt-Gruber, Irene; Ziesak, Alexandra Sabrina; Rominger, Frank; Hofmann, Peter (Organometallics, 2011)
A series of sterically and electronically fine-tuned, chelating diphosphine ligands were synthesized. The ligands are analogues of Triptyphos (TTP, 1), all based upon a variably 9,10-two-carbon-bridged 9,10-dihydroanthracene scaffold. These new TTP-type ligands were employed in the Ni(0)-catalyzed isomerization of 2-methyl-3-butenenitrile (2M3BN), one of the key steps of industrial adiponitrile production by the DuPont process. The reaction showed a surprising preference for ligands bearing electron-donating substituents, such as methoxy or methyl groups, in the phenyl para position of the Ni-ligating PPh2 units. Octyltriptyphos (3) afforded the highest 2M3BN-isomerization turnover rate yet reported. A series of deuterium-labeling experiments was performed to investigate the possibility of an isomerization mechanism consisting of a cascade of de- and rehydrocyanation steps, which could be excluded. Using the ethano-bridged ligand 4, complex 16a (4-κP:κP′)Ni(η3-C4H7)CN (supposedly an intermediate of the 2M3BN-isomerization reaction) was isolated, and its solid-state structure was determined by X-ray diffraction analysis. The complete catalytic cycle of 2M3BN isomerization with ligand 4, as suggested by the available experimental evidence, was modeled using DFT methods.
Gesehen am 26.10.2022